2016
DOI: 10.1111/1467-9817.12091
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of executive function on reading comprehension in young adults

Abstract: The purpose of this study was to examine what components of executive function (EF)inhibition, shifting and updating/working memorypredict reading comprehension in young adults. Ninety university students (65 females, 25 males; mean age = 21.82 years) were assessed on shifting (Planned Connections and Colour/Shape Shifting), inhibition (Colour-Word Stroop and Number Stroop), updating/working memory (Digit Memory and Listening Span), reading fluency (Word Reading Efficiency), vocabulary (Peabody Picture Vocabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 70 publications
(134 reference statements)
2
41
0
2
Order By: Relevance
“…Finally, planning can be seen as the ability to decide which actions are necessary to efficiently reach and complete a goal (Cartwright, 2009), and has been shown to significantly account for variation in reading comprehension, after controlling for decoding, language skills, and working memory in 9-to 15-year-olds (Cutting et al, 2009;Sesma et al, 2009). Similarly, Georgiou and Das (2018) demonstrated a contribution of planning to reading comprehension in young adults (M = 21.82 year). It has been proposed that good planners regularly monitor whether their text representations are correct and if not, may even change strategies, to achieve a correct understanding of the text (Cartwright, 2015).…”
Section: Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, planning can be seen as the ability to decide which actions are necessary to efficiently reach and complete a goal (Cartwright, 2009), and has been shown to significantly account for variation in reading comprehension, after controlling for decoding, language skills, and working memory in 9-to 15-year-olds (Cutting et al, 2009;Sesma et al, 2009). Similarly, Georgiou and Das (2018) demonstrated a contribution of planning to reading comprehension in young adults (M = 21.82 year). It has been proposed that good planners regularly monitor whether their text representations are correct and if not, may even change strategies, to achieve a correct understanding of the text (Cartwright, 2015).…”
Section: Planningmentioning
confidence: 99%
“…To our knowledge, only a few studies have examined both direct and indirect effects of executive functions on reading comprehension via decoding or language skills. These include studies with adults (Follmer & Sperling, 2019;Georgiou & Das, 2018), young adolescents (Ober et al, 2019), and children (Kieffer et al, 2013). However, the results across these studies vary, which may be explained by several factors.…”
Section: Indirect and Direct Contribution Of Executive Functions To Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, most previous studies examining the contribution of inhibition and shifting to mathematics skills have administered speeded measures of both, without controlling for the effects of speed of processing. As van der Sluis et al (2007) , and more recently Georgiou and Das (2018) have indicated, in this kind of studies unless researchers control for speed of processing we do not know if the effects of EF on mathematics are driven by their executive processing demands or by speed. Most of the EF tasks, especially the inhibition and shifting tasks, are speeded because of ceiling effects in accuracy (e.g., Anderson, 2002 ; Lee et al, 2012 ).…”
Section: Introductionmentioning
confidence: 98%
“…general mechanisms involved in reading comprehension: reasoning (Siddiqui et al, 1998;Schatschneider et al, 2007;Tiu et al, 2003), working memory capacity (Just & Carpenter, 1992;McVay & Kane, 2012, Unsworth & McMillan, 2013, perceptual/processing speed (Caplan et al, 2011;Joshi & Aaron, 2000;Payne & Stine-Morrow, 2014), and inhibition (Arrington et al, 2014;Georgiou & Das, 2018;Kieffer et al, 2013). Additionally, many domain-specific influences have been identified: verbal fluency (Jenkins et al, 2003;Silverman et al, 2012;Speece et al, 2010), word decoding (Cutting & Scarborough, 2006;Landi, 2010;Macaruso & Shankweiler, 2010), and previous language experience (Braze et al, 2016;Cromley et al, 2010;MacDonald & Christiansen, 2002).…”
mentioning
confidence: 99%